KOREOGRAFI A’KARENA RI BENTENG PANNYUA - Nurlina Syahrir; Jamilah Jamilah (Seminar Nasional LP2M UNM, 2019)
A'karena choreography from Benteng Pannyua with the interrelation-subjective approach uses a layered pattern. The results of the study prove that this layered pattern results in a socio-cultural construction, and as an initial foundation the identities of the four ethnicities are raised as a foothold in conducting research / exploration. These results were formed and constructed following the choreography concept of A'karena ri Benteng Pannyua with a duration of 1 hour 45 minutes. The symbol of the movement is realized following the spatial landscape in the Fort Rotterdam Rotterdam, all of which are divided into three stages of time namely morning, evening and night atmosphere. In the morning until noon the emphasis on the educational atmosphere, the afternoon until before sunset point points on the religious atmosphere and at night the atmosphere of the fort will be conditioned as its function in the past until now as the public space of the people of South Sulawesi. The purpose of this study is to create the A'karena ri choreography of Benteng Pannyua with the understanding that, the body becomes a point of view in seeing all the problems and the elements in them. Motion, sound, light, body, space-time interact in multiple dimensions. The first four elements are interrelated bases, the other two elements namely space and time are also one frame. In this sense, in fact four are one and two are one, all of which are in unity, as the basis for activity. In this dance work the